Prevalence of methicillin‐resistant Staphylococcus aureus among health care workers of intensive care units in Ecuador - Alejandra Ruiz; Marcelo Mora; Camilo Zurita; Danny Larco; Yadira Toapanta; Jeannete Zurita (Journal of Infection in Developing Countries)
Introduction: Colonization of health care workers with methicillin-resistant Staphylococcus aureus (MRSA) has been an important route of dispersion and infection of MRSA and has been implicated in epidemic outbreaks. The objective of the present study was to assess prevalence of MRSA colonization in the anterior nares of health care personnel at the intensive care unit (ICUs) of three hospital facilities in Quito, Ecuador. Methodology: The prevalence of MRSA in specimens from all ICU health care workers of three hospitals was measured by using a real-time PCR assay and CHROMagar MRSA. Results: The prevalence of MRSA among the three health care facilities was 2.4%. Conclusion: The prevalence of MRSA colonization was relatively low compared to other studies and showed no differences between hospital facilities.